Cognitive approach and psycholinguistics of reading: design and validation of a test of reading skills in the children of Callao, Perú - Velarde, Esther (2010)
This study was based on the psycholinguistics and cognitive theory believes that learning to read, candidates must have achieved a level of development in phonological awareness, knowledge of written language, verbal memory and semantic and syntactic levels of language oral. In this article we raised the consideration of these variables as predictors of learning reader in first grade children entering primary schools in the region of Callao. To fulfill that purpose, we designed and validated TEST PRE-READING SKILLS (THP), consisting of four subtests, the first to evaluate phonological awareness, the second, which assesses knowledge of the name and sound of the letters, the third which assesses verbal memory, and finally, the fourth which assesses the syntactic and semantic components of oral language. Reliability was estimated by Cronbach’s alpha and Spearman-Brown coefficient. Was determined construct validity using factor analysis. Finally, predictive validity was found correlated with the Assessment Battery-Revised reading process (Cuetos F. 2007). It offers the professional academic and an instrument to predict the level of learning to read to intervene in areas deficient.